2018
DOI: 10.1016/j.trgeo.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding track substructure behavior: Field instrumentation data analysis and development of numerical models

Abstract: Numerous studies have targeted using numerical modeling, field instrumentation, or combinations of both to gain insight into track substructure behavior under loading. In-depth understanding of track substructure behavior serving both passenger and freight trains is critical to developing suitable design and maintenance/rehabilitation methods to ensure adequate performance under loading. This manuscript presents findings from a recently completed study involving advanced instrumentation and numerical modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Note that validation of this model was carried out using field instrumentation data collected as part of a research project undertaken at the University of Illinois that focused on investigating different factors contributing to the problem of differential movement at track transitions. Findings from the above-mentioned research project have been presented in multiple manuscript over the past decade (Mishra et al, 2012;Tutumluer et al, 2012;Mishra et al, 2014;Mishra et al, 2016;Tutumluer et al, 2016;Boler et al, 2018;Hou et al, 2021). In-line with the field instrumentation effort, a point lying 18.3-m (60-ft.) away from the bridge abutment was taken to present OTL, whereas a point lying at a distance of 4.6 m (15 ft) from the bridge abutment was taken as being representative of NBL.…”
Section: Development Of Discretely Supported Train-track-bridge Modelmentioning
confidence: 91%
See 1 more Smart Citation
“…Note that validation of this model was carried out using field instrumentation data collected as part of a research project undertaken at the University of Illinois that focused on investigating different factors contributing to the problem of differential movement at track transitions. Findings from the above-mentioned research project have been presented in multiple manuscript over the past decade (Mishra et al, 2012;Tutumluer et al, 2012;Mishra et al, 2014;Mishra et al, 2016;Tutumluer et al, 2016;Boler et al, 2018;Hou et al, 2021). In-line with the field instrumentation effort, a point lying 18.3-m (60-ft.) away from the bridge abutment was taken to present OTL, whereas a point lying at a distance of 4.6 m (15 ft) from the bridge abutment was taken as being representative of NBL.…”
Section: Development Of Discretely Supported Train-track-bridge Modelmentioning
confidence: 91%
“…Although detailed discussion of different factors governing poor performance of track transitions is not the primary focus of this manuscript, this aspect has been discussed in great details by the following researchers: Li and Davis (2005), Tutumluer et al (2012), Mishra et al (2014), Mishra et al (2017), and Boler et al (2018). According to Nicks (2009), remedial measures aimed at mitigating the bump problem at railway bridges can be divided into different interrelated categories, such as: 1) reducing approach settlement, 2) decreasing the track modulus on the bridge deck, 3) increasing the modulus of the approach section, 4) reducing ballast wear and movement, and 5) increasing track damping on the bridge deck.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have conducted field investigations in the track transitions to understand their behavior and have identified the probable causes of the associated problems (Li and Davis, 2005;Stark and Wilk, 2015;Coelho et al, 2017;Boler et al, 2018;. These investigations revealed that the root cause of the problem needs to be identified before applying an appropriate mitigation measure.…”
Section: Introductionmentioning
confidence: 99%
“…Railway tracks are known to show higher degradation rates at transition zones between sections with different characteristics and support conditions, i.e., between embankment and bridges, tunnels, or other structures (ERRI, 1999;Banimahd et al, 2012;Varandas et al, 2014a;Paixão et al, 2013;Boler et al, 2018). These locations often exhibit differential settlements that develop during the life cycle of the track due to multiple structural and geo-mechanical reasons.…”
Section: Introductionmentioning
confidence: 99%